2016
DOI: 10.1215/00127094-3674103
|View full text |Cite
|
Sign up to set email alerts
|

Polynomials vanishing on Cartesian products: The Elekes–Szabó theorem revisited

Abstract: Let F ∈ C[x, y, z] be a constant-degree polynomial, and let A, B, C ⊂ C be finite sets of size n. We show that F vanishes on at most O(n 11/6 ) points of the Cartesian product A × B × C, unless F has a special group-related form. This improves a theorem of Elekes and Szabó [4], and generalizes a result of Raz, Sharir, and Solymosi [13]. The same statement holds over R, and a similar statement holds when A, B, C have different sizes (with a more involved bound replacing O(n 11/6 )).This result provides a unifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 37 publications
(97 reference statements)
2
64
0
Order By: Relevance
“…Elekes and Rónyai [3] and Elekes and Szabó [4] pioneered the study of algebraic structures behind problems from combinatorial geometry. The main result of [4] was quantitatively improved by the authors in [15] to the following statement; we state it here in a somewhat rough form, and refer to [15] for a full and precise statement. Given an irreducible polynomial F ∈ C[x, y, z] and finite sets A, B, C ⊂ C of size n, we have the bound (writing Z(F ) for the zero set of F )…”
Section: Introductionmentioning
confidence: 84%
“…Elekes and Rónyai [3] and Elekes and Szabó [4] pioneered the study of algebraic structures behind problems from combinatorial geometry. The main result of [4] was quantitatively improved by the authors in [15] to the following statement; we state it here in a somewhat rough form, and refer to [15] for a full and precise statement. Given an irreducible polynomial F ∈ C[x, y, z] and finite sets A, B, C ⊂ C of size n, we have the bound (writing Z(F ) for the zero set of F )…”
Section: Introductionmentioning
confidence: 84%
“…Elekes and Szabó [6] showed that if the polynomial is not degenerate in this sense, then the bound (1) can be improved to n 2−η for some η > 0. A quantitative improvement to η = 1/6 was obtained by Raz, Sharir and de Zeeuw [9], leading to the following statement. 6,9]).…”
Section: Introductionmentioning
confidence: 78%
“…A quantitative improvement to η = 1/6 was obtained by Raz, Sharir and de Zeeuw [9], leading to the following statement. 6,9]). Let F ∈ R[x, y, z] be a polynomial of degree d. If F is not degenerate, then for any A, B, C ⊂ R of size n we have…”
Section: Introductionmentioning
confidence: 78%
“…Theorem generalizes many problems from discrete geometry and additive combinatorics, and so has many applications (for example, see or ). While we will not aim to give a complete background, it is important to also mention that the analogous problem has been considered over different fields instead of double-struckR, where many interesting results are also available.…”
Section: Introductionmentioning
confidence: 99%
“…Let d be a positive integer, let A, B ⊂ R be finite sets, and let f ∈ R[x, y] be of degree d. Then, unless f = h(g 1 (x) + g 2 (y)) or f = h(g 1 (x) · g 2 (y)) for some h, g 1 , g 2 ∈ R[x], we have f (A, B) = min |A| 2/3 |B| 2/3 , |A| 2 , |B| 2 . Theorem 1.1 generalizes many problems from discrete geometry and additive combinatorics, and so has many applications (for example, see [10] or [11]). While we will not aim to give a complete background, it is important to also mention that the analogous problem has been considered over different fields instead of R, where many interesting results are also available.…”
mentioning
confidence: 99%